Determinants Of Young Entrepreneurial Success: The Role Of Digital Literacy, Locus Of Control, And Entrepreneurship Education - Muhammad Iqbal Baihaqi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to analyze the influence of digital literacy, locus of control, and entrepreneurship education on entrepreneurial performance using quantitative methods and accidental sampling techniques. Validity, reliability, and determination coefficients were tested using PLS SEM SmartPLS-3. The results of the study showed that the three variables had a positive effect on entrepreneurial performance, with the locus of control providing the most significant influence. Based on the results of the study, it was found that the locus of control plays an important role in encouraging the improvement of entrepreneurial performance.